PENGARUH KUALITAS LAYANAN KESEHATAN IBU DAN ANAK TERHADAP LOYALITAS PASIEN PADA POLI KEBIDANAN RUMAH SAKIT UMUM DAERAH KABUPATEN BREBES - Lusia Wulandari Sutejo; Eti Junaeni (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2018)
This study aims to determine the effect of the quality of maternal and child health services on loyalty of patients In Poly Kebidanan General Hospital District Brebes. By using 100 respondents (one hundred) patients and with the help of SPSS program to analyze the data obtained partial test results (t test) shows the value of t arithmetic of 12.441 is greater than t table of 1.984 or (12,441> 1,984) which means that the quality health services significantly influence the loyalty of patients in Poly Kebidanan General Hospital District Brebes. While based on Rank Spearman test results obtained r value of 0.785 means the correlation between service quality with loyalty is positive and strong. Keywords: service quality, patient loyalty